Equilibrative Nucleoside Transporters-1 Inhibitors Act as Anti-epileptic Agents by Inhibiting Glutamatergic Transmission - Ho, Shih-Yin; Chen, I-Chun; Chang, Kai-Chieh; Lin, Hsiao-Ru; Tsai, Che-Wen; Lin, Chun-Jung; Liou, Horng-Huei (Frontiers in Neuroscience, 2020)
Epilepsy is associated with adenosine dysregulation, and equilibrative nucleoside transporters-1 (ENT-1) functions as a regulator of extracellular adenosine. This study aimed to prove anti-epileptic effect of ENT-1 inhibitors JMF1907 and J4 on animal models of various epilepsy, and the possible mechanism of the drug. Maximal electroshock seizure (MES), pentylenetetrazol (PTZ)-induced seizure and kindling models was used as mouse model of generalized tonic-clonic epilepsy, generalized myoclonic epilepsy, and partial epilepsy. The epilepsy frequency, duration, and Racine score were then evaluated. Whole-cell recordings were made from the hippocampal dentate granule cells by using a patch-clamp technique in the brain slice of the mice. In MES, JMF1907 at a dose of 5 mg/kg was efficacious in decreased hindlimb extension, while J4 did not decrease hindlimb extension until a higher dose (10 mg/kg). Both JMF1907 and J4 are potent in lengthening onset latency in PTZ-induced myoclonic epilepsy model, but ethosuximide (ETH) had better effects on the Racine score. In kindling model, JMF1907 and J4 at a dose of 1 mg/kg had effects on seizure frequency and duration, and the effects of JMF1907 was comparable with carbamazepine. Both JMF1907 and J4 can reduce the glutamatergic spontaneous excitatory postsynaptic currents (sEPSCs) frequency. The maximal inhibition was about 50% for JMF1907 at a concentration of 1 ug/L, whereas J4 can only inhibited 40% of sEPSCs frequency at a dose of 10 ug/L. ENT-1 inhibitor JMF1907 and J4 showed anti-epileptic effects in different epilepsy models. Their effects possibly act on pre-synaptic neuronal modulation.